The Effect of Financial Performance and Reinsurance on The Deficit in The Balance of Payments of Insurance in Indonesia - Erike Anggraeni; Gustika Nurmalia; Dewi Tradena (International Business and Accounting Research Journal, 2022)
Insurance regulation in Indonesia is important to be implemented because the balance of payments for insurance services is in deficit. The insurance industry in Indonesia does not have sufficient capacity to absorb all potential risks exist in the country so that it partners with foreign assurers which then has an impact on the balance of payments deficit. If not addressed immediately, it will harm the country's economy so prosperity will be difficult to achieve. This study aims to see the effect of financial performance and reinsurance on the insurance balance of payments deficit in Indonesia. The method used in this study was quantitative using secondary data in the form of time-series data obtained from the Financial Services Authority. Data collection uses documentation in the form of quarterly data starting from 2010Q1-2019Q4. The total sample was 40 samples. The collected data was then analyzed using multiple-linear regression. The results of this study indicate that financial performance and reinsurance have a significant effect simultaneously and partially on the deficit in the insurance balance of payments in Indonesia. The coefficient of determination of 0.507 or 50.7%, means that the ability of independent variables; financial performance and reinsurance in explaining the deficit in insurance balance of payments in Indonesia for the 2010-2019 period was 50.7% and 49.3% was influenced by other variables that were not studied.